2018
DOI: 10.1016/j.celrep.2018.11.052
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-8 Favors the Presentation of Surface-Tethered Antigens by Stabilizing the B Cell Immune Synapse

Abstract: SummaryComplete activation of B cells relies on their capacity to extract tethered antigens from immune synapses by either exerting mechanical forces or promoting their proteolytic degradation through lysosome secretion. Whether antigen extraction can also be tuned by local cues originating from the lymphoid microenvironment has not been investigated. We here show that the expression of Galectin-8—a glycan-binding protein found in the extracellular milieu, which regulates interactions between cells and matrix … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 58 publications
2
19
0
Order By: Relevance
“…Since actin remodeling was shown to be involved in antigen pinocytosis of newly activated DCs (West et al, 2004), it is conceivable to pose that Gal-8-induced cell spreading could also participate in antigen uptake enhancement. In support of our findings, Obino et al (2018) have reported that exposure of specific B cells to particulate-antigen coated with Gal-8 increased their internalization capacity in vivo, reinforcing a role for extracellular Gal-8 in favoring the phagocytosis process as well.…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Since actin remodeling was shown to be involved in antigen pinocytosis of newly activated DCs (West et al, 2004), it is conceivable to pose that Gal-8-induced cell spreading could also participate in antigen uptake enhancement. In support of our findings, Obino et al (2018) have reported that exposure of specific B cells to particulate-antigen coated with Gal-8 increased their internalization capacity in vivo, reinforcing a role for extracellular Gal-8 in favoring the phagocytosis process as well.…”
Section: Discussionsupporting
confidence: 89%
“…Co-administration of recombinant Gal-8 and inactivated foot-and-mouth disease virus (FMDV) elicited a major protective antibody-mediated response in BALB/cJ mice, compared with the immunization with only viral antigen (Carabelli et al, 2017). In agreement with our findings, Obino et al (2018) showed that exogenously added Gal-8 is able to increase the number of antigen-specific germinal center B cells and T follicular helper cells. As a mechanism of action, these authors demonstrated that Gal-8 enhances particulate-antigen acquisition by B cells in vivo, promoting its presentation by stabilizing the B-immune synapse and enhancing B cell responses.…”
Section: Access Isciencesupporting
confidence: 85%
See 1 more Smart Citation
“…S6A-B). Furthermore, the APC ability of Drd3 +/+ and Drd3 -/-B-cells was evaluated in vitro using huMOG-coupled beads as antigen and CD4 + T-cells expressing a MOG-specific TCR as described before 54 . The results show that Drd3-deficiency in Bcells did not affect neither T-cell proliferation nor T-cell differentiation (Fig.…”
Section: Drd3-stimulation In B-cell Favours the Acquisition Of Cxcr3 mentioning
confidence: 99%
“…The extent of cell death was quantified using the ZAq Fixable Viability kit (Biolegend).In vitro Antigen presentation assays. huMOG protein or pMOG35-55 were coupled to glutaraldehyde-activated amino beads (40x10 6 beads for 20 g huMOR or pMOG) together with F(ab')2 anti-mouse-IgM fragments in equal concentrations, as previously described(Obino, 2018). Splenic CD19 + B-cells were sorted from Drd3 +/+ or Drd3 -/animals and then incubated with huMOG-or pMOG35-55-coated beads in a B-cell-to-bead ratio 1:1 for 5h at37°C to allows the uptake and processing of antigens.…”
mentioning
confidence: 99%